The Qur'an Code: Strategi Iḥyā’ Al-Qur'an untuk Dakwah yang Tak Lekang Zaman - Alfikriah, Nurul Fathanah; Ghany , Abdul; Rosmini (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2025)
The primary challenge of contemporary Islamic propagation (dakwah) is maintaining the relevance of the Qur'anic message amidst the changing times. This study aims to dissect a strategic formulation in the effort to revive the values of the Qur'an (Iḥyā’ Al-Qur’an) as an epistemological foundation for propagation that remains current. Through a qualitative research method with a library research approach, this study analyzes the Living Qur'an framework as a concrete manifestation of Iḥyā’ Al-Qur’an, which integrates the dimensions of text, interpretation, and the sociocultural reality of the Muslim community. The findings indicate that this approach serves as an operational "code" that translates revelation into dynamic life practices, subsequently strengthening the spiritual resilience and social cohesion of the community. Its implementation in community-based education and empowerment programs has proven capable of internalizing Qur'anic values more profoundly. Thus, the Iḥyā’ Al-Qur’an strategy offers a paradigm for sustainable propagation, where the Islamic message does not stop at knowledge transmission but undergoes a transformation into a collectively lived ethos, thereby ensuring its continuity across generations.